Determination of the inhibitory activity of silver nanoparticles against some pathogenic multi-antibiotic resistant bacterial species - Riyam F. Saleh; Mohammed N. Maaroof; Haider M. Hamzah (Tikrit Journal of Pure Science)
The study was done to determine the inhibitory effect of silver nanoparticles synthesed by the filamentous fungus Fusarium mangiferae against some multidrugs resistant pathogenic bacteria which were taken from the Central Laboratory of Sulaymaniyah Teaching Hospital.Silver nanoparticles showed their inhibitory effect on the various bacterial species in this study by two methods Wich are the well diffusion method and inhibition growth. Nanoparticles of silver showed inhibitory areas by Well diffusion method against Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Proteus mirabilis.